Implementasi Balance Scorecard dalam Menciptakan Pengelolaan Dana yang Good Organization Governance Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tulungangung - Ningtyas, Dwi Wahyu; Nabawy, Nuhan; Bahusayekti, Krisna (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
The implementation of balance scorecard in order to further empower the management of zakat funds into Good Organization Governance at BAZNAS Tulungagung Regency has been implemented well but needs to be maximized. When viewed from a financial perspective it has been implemented well. Meanwhile, from a customer perspective based on customer satisfaction in receiving services from BAZNAS Tulungagung Regency, it has been carried out well in accordance with the vision, mission and goals of the organization. The internal business perspective which includes learning, ability to change, handling customer complaints, the time it takes to handle complaints and organizational accountability is also considered good but not optimal because it is not profit-oriented but for worship. The growth and learning perspective based on employee satisfaction as human capital for the organization shows that employees who work at BAZNAS Tulungagung Regency are relatively still based on worship factors, the loyalty shown by employees and efforts to learn by themselves are based on worship and seeking the pleasure of Allah SWT alone. From these existing problems, it is hoped that BAZNAS Tulungagung Regency can create more programs that make mustahik more productive so that they can alleviate poverty in Tulungagung Regency. In terms of collecting the next ZIS funds, it is hoped that it will be made digitally to make it easier for muzaki to carry out zakat and expand the reach of prospective muzaki (tulungagung residents) who are outside the city or abroad. In this study, researchers used descriptive qualitative research methods, namely research that solely describes (describes) the circumstances and events of an object described in full, detailed and clear.